Modeling Trienzyme Biosensor at Internal Diffusion Limitation - Kulys, J. (Nonlinear Analysis: Modelling and Control, 2004)
A model of biosensor containing three immobilized enzymes utilizing consecutive substrate conversion in the chain was developed. The modeling was performed at an internal diffusion limitation and a steadystate condition. The calculations showed that significant response of biosensors was produced if diffusion modules were larger than 1 for all enzyme reactions. Due to diffusion limitation the apparent stability of biosensor response increased many times in comparison to stability of the most labile enzyme of the chain.
Keywords: biosensor; modeling; polyenzymes